Inhibitory and preventive effects of Arnebia euchroma (Royle) Johnst. root extract on Streptococcus mutans and dental caries in rats - Zeyu Wu; Jie Song; Yangyang Zhang; Xiyu Yuan; Jin Zhao (Nature Publishing Group, 2024)
Abstract Background Dental caries is one of the prevalent conditions that threaten oral health. Arnebia euchroma (Royle) Johnst. root (AR) extracts exhibit anti-inflammatory, anti-cancer, and antibacterial properties. This study was designed to investigate the antibacterial impact of AR extract on Streptococcus mutans (S. mutans) UA159 and the anti-caries effect on rats. Methods The antibacterial activity of AR extract against S. mutans and its biofilm was determined using the bacterial sensitivity test, the biofilm sensitivity test, and the live-dead staining technique. By fluorescently tagging bacteria, the influence of bacterial adhesion rate was determined. Using a rat caries model, the anti-caries efficacy and safety of AR extract were exhaustively investigated in vivo. Results AR extract inhibit not only the growth of S. mutans, but also the generation of S. mutans biofilm, hence destroying and eliminating the biofilm. Moreover, AR extract were able to inhibit S. mutans' adherence to saliva-encapsulated hydroxyapatite (HAP). Further, in a rat model of caries, the AR extract is able to greatly reduce the incidence and severity of caries lesions on the smooth surface and pit and fissure of rat molars, while exhibiting excellent biosafety. Conclusions AR extract exhibit strong antibacterial activity against S. mutans and can lower the incidence and severity of dental cavities in rats. These findings suggest that Arnebia euchroma (Royle) Johnst. could be utilized for the prevention and treatment of dental caries.